(untitled) (Bangladesh Journal of Botany, 2025)
Field experiment was carried out to assess the efficacy of herbicides for control of weeds in wheat.The dominant weed flora in wheat were Cynodon dactylon, Cyperus rotundus, Chenopodium album, Medicago denticulate, Anagallis arvensis and Launaea nudicaulis. The efficacy of herbicides pendimethalin 1000 g/ha PE, clodinafop-propargyl 60 g/ha and sulfosulfuron 25 g/ha was poor, which improved with the increase combined application of herbicides. However, combined application of post emergence sulfosulfuron + metsulfuron-methyl 20 + 4 g/ha and clodinafop-propargyl + metsulfuron-methyl 60 + 4 g/ha were significantly superior in reducing dry weight of both broad leaved and grassy weeds. The highest grain yield was recorded under weed free followed by clodinafop-propargyl + metsulfuron-methyl 60 + 4g/ha. Among the weed control treatments, maximum net returns of 87235/ha and highest B : C ratio (2.97) was recorded in clodinafop-propargyl + metsulfuron-methyl 60 + 4 g/ha. Bangladesh J. Bot. 54(3): 581-585, 2025 (September)